Thermal environment in two broiler barns during the first three weeks of age - Robinson Osorio H.; Ilda F. F. Tinoco; Jairo A. Osorio S; Luciano B. Mendes; Keller S. O. Rocha; Lina M. Guerra G. (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this research was to evaluate the internal thermal environment of two broiler barns featuring different ventilation systems representative of Brazilian and South American poultry production industry: (a) a negative-pressure tunnel and (b) a positive-pressure lateral ventilation system. Environmental parameters such as dry bulb temperature, relative humidity and temperature-humidity index were assessed; temperature maps for day and night average conditions were determined for the first three weeks of life. Better uniformity of the thermal environment and comfort conditions inside the negative-pressure tunnel were found.